1985
DOI: 10.1002/jnr.490130115
|View full text |Cite
|
Sign up to set email alerts
|

Guidance of neurite outgrowth by pathways of substratum‐adsorbed laminin

Abstract: Neurite outgrowth is guided by narrow pathways of bioactive laminin. These pathways are created by ultraviolet light irradiation of laminin-coated coverslips masked with electron microscope grids. Patterned outgrowth of neurites is independent of gross mechanical guidance and guidance caused by substrate limitation. Cells on unirradiated laminin are less readily displaced by shear forces than cells on irradiated laminin. This study suggests that ultraviolet light alters the adhesive properties of laminin and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
118
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(121 citation statements)
references
References 17 publications
2
118
1
Order By: Relevance
“…Cooper et al 107 vacuum deposited thin films of silicon monoxide through masks and found that mouse neuroblastoma cells NB41A adhered and neurites aligned on the silicon monoxide lines. Hammarback et al 108 created micropatterns of "bioactive" and inactive laminin by ultraviolet light inactivation of laminin-coated coverslips masked with EM grids; they found that axon growth cone guidance of chicken embryonic DRG neurons by substrate-bound laminin pathways was correlated with neuron-to-pathway adhesivity 109 By UV irradiation of agarose/albumin surface through EM grids followed with laminin absorption on the irradiated region, they also created patterns of laminin-coated (high adhesivity) surfaces interspersed with agarose/albumin (low adhesivity)-coated regions. 110 Neurons only adhered to the laminin-coated regions, but some neurites extended across intervening agarose/ albumin regions, supporting the guidepost hypothesis for pioneer axon pathfinding.…”
Section: Vb Neuronal Cell Biology On a Chipmentioning
confidence: 99%
“…Cooper et al 107 vacuum deposited thin films of silicon monoxide through masks and found that mouse neuroblastoma cells NB41A adhered and neurites aligned on the silicon monoxide lines. Hammarback et al 108 created micropatterns of "bioactive" and inactive laminin by ultraviolet light inactivation of laminin-coated coverslips masked with EM grids; they found that axon growth cone guidance of chicken embryonic DRG neurons by substrate-bound laminin pathways was correlated with neuron-to-pathway adhesivity 109 By UV irradiation of agarose/albumin surface through EM grids followed with laminin absorption on the irradiated region, they also created patterns of laminin-coated (high adhesivity) surfaces interspersed with agarose/albumin (low adhesivity)-coated regions. 110 Neurons only adhered to the laminin-coated regions, but some neurites extended across intervening agarose/ albumin regions, supporting the guidepost hypothesis for pioneer axon pathfinding.…”
Section: Vb Neuronal Cell Biology On a Chipmentioning
confidence: 99%
“…Several methods have been developed for patterning surfaces to control neuronal attachment and growth (Hammarback et al, 1985;Kleinfeld et al, 1988;Corey et al, 1991;Stenger et al, 1992;Matsuda et al, 1992;Lom et al, 1993;Hickman et al, 1994;Corey et al, 1997;Branch et al, 1998;Ravenscroft et al, 1998;Branch et al, 2000;James et al, 2000;Lauer et al, 2001). Using these techniques it is possible to direct neuron cell bodies to electrodes and thus provide the ability to study individual neurons within a neural network.…”
Section: Introductionmentioning
confidence: 99%
“…Zn vivo the ECM is involved in the migration of neural crest cells during development (Boucaut et al, 1984;Bronner-Fraser, 1986), as well as in the regeneration of peripheral nerves (Sandrock and Matthew, 1987) and myoneural synapses (Nitkin et al, 1983). In cell culture, the adhesive interactions of neurons with purified ECM molecules such as collagen, fibronectin, and laminin strongly influence the extent (Akers et al, 198 1;Carbonetto et al, 1982Carbonetto et al, , 1983Man-thorpe et al, 1983) and direction (Turner and Carbonetto, 1984;Hammarback et al, 1985) of neurite growth. Laminin, in particular, stimulates neurite outgrowth from dorsal root or sympathetic ganglia, which otherwise require exogenous nerve growth factor (NGF) (Edgar et al, 1984;Lander et al, 1985).…”
mentioning
confidence: 99%